Effect of indium diffusion on characteristics of CdS films and nCdS/pSi heterojunctions - Dzhafarov, T. D.; Ongul, F.; Yuksel, S. Aydin (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Diffusion of indium in In/nCdS/glass and In/nCdS/pSi structures at 350-550 degrees C in vacuum 1.33 x 10(-1) Pa and its effect on structural, electrical, optical and photovoltaic characteristics of nCdS films, fabricated by spray pyrolysis technique and nCdS/pSi heterojunctions have been investigated. The indium-doped and undoped CdS films were characterized by X-ray diffraction (XRD), electrical and optical measurements. The concentration profiles of indium and the components of CdS films (Cd and S) in In/nCdS/pSi structures were studied using the energy dispersive X-ray fluorescence (EDXRF) analysis. The thermal annealing of In/nCdS/pSi structures is accompanied by the diffusion penetration of In through CdS film into Si substrate. At the same time, the Cd and S atoms from CdS film diffuse into Si substrate. The diffusion doping of CdS film by indium did not change the polycrystalline hexagonal structure and the energy band gap of CdS films and increased the electron concentration from 1.4 x 10(13) to 1.3 x 10(16) cm(-3). The photovoltaic parameters and spectral responsivity of In-doped nCdS(In)/pSi(In) cells were higher than those for nCdS/pSi cells and reached the maximum values after the thermal annealing at 450 degrees C. The improvement of the photovoltaic parameters of nCdS(In)/pSi(In) photocells was discussed on the base of the changes introduced in the energy band diagram of nCdS/pSi heterojunction due to the indium diffusion. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: CdS/Si heterojunction; Spray pyrolysis; In diffusion; CDTE THIN-FILMS; CELLS; Materials Science; Physics